2021
DOI: 10.18502/kss.v5i8.9381
|View full text |Cite
|
Sign up to set email alerts
|

A New Strategic Business Expectancy for MSME Sustainability: The Impact of Uncertainty During the COVID-19 Pandemic

Abstract: The COVID-19 pandemic has led to a significant economic crisis. Production activities have stopped, people’s purchasing power has decreased, and the fall in the stock market has led to uncertainty. MSMEs need to maintain business continuity during a pandemic to exist after the pandemic is over. The purpose of this research was to analyze the impact of COVID-19 on MSMEs and to suggest several strategies to maintain business continuity. Qualitative research methods and a thematic analysis approach were used to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 3 publications
1
2
0
3
Order By: Relevance
“…It is also found from the interview that about 88% of the respondents ranked loan repayment issues as the top problem. This is consistent with recent research findings of Prameka, Sudarmiatin, Wiraguna, Prabowo, and Do (2021) that there were some problems and difficulties that entrepreneurs faced during the Covid-19 pandemic such as financial distress particularly on debt management and inability to pay obligation.…”
Section: Introductionsupporting
confidence: 93%
“…It is also found from the interview that about 88% of the respondents ranked loan repayment issues as the top problem. This is consistent with recent research findings of Prameka, Sudarmiatin, Wiraguna, Prabowo, and Do (2021) that there were some problems and difficulties that entrepreneurs faced during the Covid-19 pandemic such as financial distress particularly on debt management and inability to pay obligation.…”
Section: Introductionsupporting
confidence: 93%
“…Seluruh narasumber sudah menjalankan inovasi produk walaupun belum semua ide bisa diwujudkan. Pada masa pandemi ini para pemilik bisnis khususnya usaha mikro perlu secara berkala memberikan inovasi walaupun banyak peraturan new normal yang membuat proses merealisasikan menjadi lebih terbatas (Prameka, Sudarmiatin, Wiraguna, Prabowo, & Do, 2021).…”
Section: Profitabilityunclassified
“…Salah satu kendala usaha mikro adalah ketersediaan sumber daya manusia yang kompeten di bidangnya (Prameka et al, 2021). Beragam hal dilakukan oleh para narasumber untuk mencapai target usahanya seperti melakukan promosi di media sosial dan melakukan inovasi dalam produk dan kualitas layanan.…”
Section: Firm Survivalunclassified
See 1 more Smart Citation
“…They attribute this to a top-down planning and management approach, arguing that this model poses a main barrier to sustainable relationships among ecotourism stakeholder groups (Murphy, 1985). While an extensive body of academic literature (Gumede and Nzama, 2020;Ying and Zhou, 2007;Chili and Ngxongo, 2017;Prameka et al, 2021;Xiong et al, 2021;Nugraha, 2021) highlights the significance of local community participation in ecotourism development, numerous studies (e.g., Mustapha et al, 2013;Marzuki et al, 2012;Dogra and Gupta, 2012;Snyman, 2016;Wang et al, 2015;Wen and Ximing, 2008) found manipulative participation to be dominant in most tourist destinations, including some in South Africa. Moreover, there is a paucity of academic research in the field of sustainable ecotourism development in KwaZulu-Natal.…”
Section: Introductionmentioning
confidence: 99%